2022
DOI: 10.1038/s41467-021-27806-3
|View full text |Cite
|
Sign up to set email alerts
|

Alcohols electrooxidation coupled with H2 production at high current densities promoted by a cooperative catalyst

Abstract: Electrochemical alcohols oxidation offers a promising approach to produce valuable chemicals and facilitate coupled H2 production. However, the corresponding current density is very low at moderate cell potential that substantially limits the overall productivity. Here we report the electrooxidation of benzyl alcohol coupled with H2 production at high current density (540 mA cm−2 at 1.5 V vs. RHE) over a cooperative catalyst of Au nanoparticles supported on cobalt oxyhydroxide nanosheets (Au/CoOOH). The absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 59 publications
(63 reference statements)
2
132
0
7
Order By: Relevance
“…This phenomenon may be associated with the higher activity of π‐bond‐containing alcohols (in terms of potential at 1 mA cm −2 , Figure S30f), and the competition between alcohol oxidation and aldehyde oxidation during the electrocatalytic BDAOR. Our recent work suggested that alcohols with π bond, such as benzyl alcohol and β‐phenylethanol, are more active than the alcohols without π bond, because the energy levels of the highest occupied molecular orbital (HOMO) for π‐bond‐containing alcohols are higher, which means that these alcohols are more likely to be oxidized [52] . The higher activity of π‐bond‐containing alcohol reactant would enable a more favorable kinetics of alcohol oxidation than aldehyde oxidation, and thus suppresses the further oxidation of aldehyde product during electrocatalysis, finally leading to a higher yield of aldehyde product.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may be associated with the higher activity of π‐bond‐containing alcohols (in terms of potential at 1 mA cm −2 , Figure S30f), and the competition between alcohol oxidation and aldehyde oxidation during the electrocatalytic BDAOR. Our recent work suggested that alcohols with π bond, such as benzyl alcohol and β‐phenylethanol, are more active than the alcohols without π bond, because the energy levels of the highest occupied molecular orbital (HOMO) for π‐bond‐containing alcohols are higher, which means that these alcohols are more likely to be oxidized [52] . The higher activity of π‐bond‐containing alcohol reactant would enable a more favorable kinetics of alcohol oxidation than aldehyde oxidation, and thus suppresses the further oxidation of aldehyde product during electrocatalysis, finally leading to a higher yield of aldehyde product.…”
Section: Resultsmentioning
confidence: 99%
“…Then the intermediate state of dihydroxybenzenes was oxidized by V 5+ to hydroquinone or catechol in the proton transfer process. 50,51 As the reaction proceeded, a small amount of HQ was overoxidized to form p -benzoquinone (Fig. 8b III).…”
Section: Resultsmentioning
confidence: 99%
“…One of the oxidation products, benzoic acid (BAc), with high value, can serve as a versatile intermediate in manufacturing flavor ingredients and cosmetical preservatives. According to the literature, the electrooxidation of BA into BAc possesses a lower thermodynamical potential than that of OER, [103,104] thus, the benzyl alcohol oxidation reaction (BAOR) also has been employed in HWE for highly efficient H 2 production with concurrent BAc (or in the form of salt) production in alkaline media lately. Sun's group firstly used the 3D porous nickel framework (hp-Ni) as a bifunctional electrocatalyst for the refining of BA and other aromatic alcohols (e.g., 4-nitrobenzyl alcohol, 4-methylbenzyl alcohol) integrated with the HER under alkaline condition.…”
Section: Benzyl Alcoholmentioning
confidence: 99%